Oleic acid modified oxide graphene/triazine-based covalent-organic frameworks composite: Cooperation between heterostructure and electrical double layer to enhance tribological performances. (February 2023) - Yan, Qianqian; Ma, Haojie; Zhang, Duo; Wen, Ping; Fan, Mingjin
Abstract: Designing novel additives to construct the lubrication film integrating multi-configuration provides a promising solution for developing the lubricants with the excellent tribological performances. Present work prepared the oleic acid-modified graphene oxide/triazine-based covalent-organic frameworks composite (o-GTC) via a two-step solvothermal reaction as a dispersible additive to PAO 10 oil. The XRD, FTIR, Raman and SEM analyses characterized the heterostructure of the o-GTC. Tribological tests reveal that an optimum dose of o-GTC (0.05 wt%) dramatically decreased friction and wear by 50.9% and 92.9% for steel tribopair. The investigation of worn scar uncovered that the firm and tenacious lubrication film integrating the electrical double layer and the heterostructure is formed on the sliding surface, which is responsible for the outstanding tribological performances. Graphical Abstract: Electrical double layer and heterostructure were synchronously integrated to toughen the lubrication film to improve tribological performances, applying oleic acid modified graphene oxide/triazine-based covalent organic frameworks composite (o-GTC) as a lubricant additive. ga1 Highlights: Oleic acid modified oxide graphene/covalent-organic frameworks composite is prepared. Modification in covalent and ionic bonds is realized simultaneously. Nano lubrication film with electrical double layer and heterostructure can be formed. Multiple enhancement effects cooperate to boost the tribological performances.